A plant design on the manufacture of sucrose ester surfactants - Fonacier, Robert Ma. S. (College of Engineering, 1982)
Plant: Sucrose Esters Manufacturing Co. -- Plant site: Calamba, Laguna -- Factory area: 6,300 sq. ft. -- Products: Sucrose cocoate, Glycerol and fatty acids -- Working days: 300 days per year -- Plant capacity: 22,340.39 lbs/day -- Total capital investment: P 43,464,901.75 -- Total product cost: P 26,554,809.18 -- Total annual sales: P 135,570,234 -- Annual profit: P 109,015,424.80 -- Break-even point: 4.40% -- Pay-out time: 4.80 months